Molecular Defense Response of Bursaphelenchus xylophilus to the Nematophagous Fungus Arthrobotrys robusta - Xin Hao; Jie Chen; Yongxia Li; Xuefeng Liu; Yang Li; Bowen Wang; Jingxin Cao; Yaru Gu; Wei Ma; Ling Ma (Cells, 2023)
Bursaphelenchus xylophilus causes pine wilt disease, which poses a serious threat to forestry ecology around the world. Microorganisms are environmentally friendly alternatives to the use of chemical nematicides to control B. xylophilus in a sustainable way. In this study, we isolated a nematophagous fungus—Arthrobotrys robusta—from the xylem of diseased Pinus massoniana. The nematophagous activity of A. robusta against the PWNs was observed after just 6 h. We found that B. xylophilus entered the trap of A. robusta at 24 h, and the nervous system and immunological response of B. xylophilus were stimulated by metabolites that A. robusta produced. At 30 h of exposure to A. robusta, B. xylophilus exhibited significant constriction, and we were able to identify xenobiotics. Bursaphelenchus xylophilus activated xenobiotic metabolism, which expelled the xenobiotics from their bodies, by providing energy through lipid metabolism. When PWNs were exposed to A. robusta for 36 h, lysosomal and autophagy-related genes were activated, and the bodies of the nematodes underwent disintegration. Moreover, a gene co-expression pattern network was constructed by WGCNA and Cytoscape. The gene co-expression pattern network suggested that metabolic processes, developmental processes, detoxification, biological regulation, and signaling were influential when the B. xylophilus specimens were exposed to A. robusta. Additionally, bZIP transcription factors, ankyrin, ATPases, innexin, major facilitator, and cytochrome P450 played critical roles in the network. This study proposes a model in which mobility improved whenever B. xylophilus entered the traps of A. robusta. The model will provide a solid foundation with which to understand the molecular and evolutionary mechanisms underlying interactions between nematodes and nematophagous fungi. Taken together, these findings contribute in several ways to our understanding of B. xylophilus exposed to microorganisms and provide a basis for establishing an environmentally friendly prevention and control strategy.